Deepening our Understanding of Quality in Australia (DUQuA): An overview of a nation-wide, multi-level analysis of relationships between quality management systems and patient factors in 32 hospitals. (3rd December 2019) - Braithwaite, Jeffrey; Clay-Williams, Robyn; Taylor, Natalie; Ting, Hsuen P; Winata, Teresa; Hogden, Emily; Li, Zhicheng; Selwood, Amanda; Warwick, Meagan; Hibbert, Peter; Arnolda, Gaston
Abstract: Objective: The Deepening our Understanding of Quality in Australia (DUQuA) project is a multisite, multi-level, cross-sectional study of 32 of the largest hospitals in Australia. This overview examines relationships between (i) organization-level quality management systems and department-level quality management strategies and (ii) patient-level measures (clinical treatment processes, patient-reported perceptions of care and clinical outcomes) within Australian hospitals. Design: We examined hospital quality improvement structures, processes and outcomes, collecting data at organization, department and patient levels for acute myocardial infarction (AMI), hip fracture and stroke. Data sources included surveys of quality managers, clinicians and patients, hospital visits, medical record reviews and national databases. Outcomes data and patient admissions data were analysed. Relationships between measures were evaluated using multi-level models. We based the methods on the Deepening our Understanding of Quality Improvement in Europe (DUQuE) framework, extending that work in parts and customizing the design to Australian circumstances. Setting, participants and outcome measures: The 32 hospitals, containing 119 participating departments, provided wide representation across metropolitan, inner and outer regional Australia. We obtained 31 quality management, 1334 clinician and 857 patient questionnaires, and conducted 2401 medical record reviews and 151 external assessments. External data via a secondary source comprised 14 460 index patient admissions across 14 031 individual patients. Associations between hospital, Emergency Department (ED) and department-level systems and strategies and five patient-level outcomes were assessed: 19 of 165 associations (11.5%) were statistically significant, 12 of 79 positive associations (15.2%) and 7 of 85 negative associations (8.2%). Results: We did not find clear relationships between hospital-level quality management systems, ED or department quality strategies and patient-level outcomes. ED-level clinical reviews were related to adherence to clinical practice guidelines for AMI, hip fracture and stroke, but in different directions. The results, when considered alongside the DUQuE results, are suggestive that front line interventions may be more influential than department-level interventions when shaping quality of care and that multi-pronged strategies are needed. Benchmark reports were sent to each participating hospital, stimulating targeted quality improvement activities. Conclusions: We found no compelling relationships between the way care is organized and the quality of care across three targeted patient-level outcome conditions. The study was cross-sectional, and thus we recommend that the relationships studied should be assessed for changes across time. Tracking care longitudinally so that quality improvement activities are monitored and fed back to participants is an important initiative that should be given priority as health systems strive to develop their capacity for quality improvement over time.